2014
DOI: 10.3923/pjbs.2014.402.407
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant Properties of Fucoidan Fractions From Sargassum tenerrimum

Abstract: The aim of the present study is conducted to evaluate the antioxidant potential and toxicity effect of polysaccharide-fucoidan from the brown seaweed Sargassum tenerrimum. Fucoidan-a sulphated polysaccharide contains fucose and sulphate as major compounds. Interestingly, various studies reported that the presence of sulphate content of the sample plays a significant role in pharmacological activities. In this study, fucoidan was fractionated by Ion exchange chromatography method and it major chemical constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…However, some species of brown algae have been found to display a high capacity to scavenge ROS and lower NO production. Marudhupandi et al [33] found that the antioxidant activity of fucoidan depended on the sulphate content of the extract. There appears to be some variability in the antioxidant capacity of algal extracts and their sulphate content [34].…”
Section: Other Antioxidant Compoundsmentioning
confidence: 99%
“…However, some species of brown algae have been found to display a high capacity to scavenge ROS and lower NO production. Marudhupandi et al [33] found that the antioxidant activity of fucoidan depended on the sulphate content of the extract. There appears to be some variability in the antioxidant capacity of algal extracts and their sulphate content [34].…”
Section: Other Antioxidant Compoundsmentioning
confidence: 99%
“…Recent studies have also demonstrated the potential of fucoidans for preventing Helicobacter pylori infection, one of the most concerning emergent foodborne pathogens affecting 50-80% of the worldwide population. The effect of fucoidan from brown algae as a potential antimicrobial against H. pylori thereby reduces the risk of associated gastric cancers (Marudhupandi, Kumar, Senthil, & Devi 2014). Laminaria spp.…”
Section: Carbohydratesmentioning
confidence: 99%
“…In vitro antioxidant capacities of fucoidan from Sargassum tenerrimum was analyzed by DPPH, superoxide radical scavenging and total antioxidant assays [41]. Antioxidant activity of SPs depends on their structural properties such as level or distribution of sulfate groups, MW, sugar composition, and stereochemistry [36].…”
Section: Antioxidant Activitymentioning
confidence: 99%